Sublethal Effects of Heavy Metals on Caddisfly Case-Building Behaviour - Dunstan, Beth (2021)
As scientists strive to understand the relationships between pollutants and ecosystems, the sublethal effects of heavy metals on aquatic invertebrates have been of increasing interest. Despite this, there are relatively few studies on this topic. To understand the current knowledge in this area, a literature review and meta-analysis were completed. Key research gaps were identified, and trends and limitations in the methodologies employed were assessed. Specifically, studies tended to be laboratory based, assessing the effects of just one metal on a single species. There was a large variation in the effects that were observed, although all 45 papers in the meta-analysis identified some degree of sublethal detriment. Great variability between studies coupled with the small sample pool, made it difficult to conduct formal meta-analysis techniques for assessing concentration-effect relationships. Standardised protocols and minimisation of biases, as well as a more integrated approach using both field and laboratory studies is suggested, in order to more easily compare and use studies to advise on environmental policy and regulations. Using the observations from both literature review and meta-analysis, a research proposal suitable for a Master of Research was completed, suggesting field and laboratory research into the sublethal effects of lead on caddisfly case building and predator avoidance behaviour.